THE IMPLEMENTATION STRATEGY OF THE SUSTAINABLE FISHING PORT CONCEPT AT CILACAP OCEAN FISHING PORT - Andriyanto, Dimas; Frimawaty, Evi; Kresning, Boma (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
The ecoport concept, or environmentally port management, is a sustainable development approach that integrates social, economic, and environmental aspects. This concept has been adopted in several developed and developing countries. In Indonesia, the ecoport concept has been applied to fishing ports, known as eco-fishing ports since 2013. However, the Cilacap Ocean Fishing Port (PPS Cilacap) was not selected as a pilot site that year, despite having adequate infrastructure and active fishing operations that meet the assessment parameters outlined in the National Fishing Port Master Plan. This study aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) related to environmental management and the socio-economic conditions of the local community, in order to formulate strategies for implementing a sustainable eco-fishing port at PPS Cilacap. Strategy development was carried out using a SWOT analysis based on observations, interviews, and questionnaire surveys. The results indicate that PPS Cilacap possesses strengths such as good environmental conditions and competent human resources, but it also faces challenges, including poorly maintained facilities, waste management issues, and limited financial resources. In conclusion, although PPS Cilacap demonstrates favorable environmental conditions and skilled personnel, improvements in maintenance, waste handling, and budget allocation are needed. Enhancing infrastructure, fostering partnerships, and advancing sustainability initiatives will be crucial to the successful implementation of the eco-fishing port concept. Keywords: Cilacap Ocean Fishing Port, eco fishing port, opportunities, strengths, threats, weaknesses